Pemahaman Modal dalam Praktik Dagang Masyarakat Muslim Gu-Lakudo di Sulawesi Tenggara - Samdin, Samdin (Universitas Brawijaya, Indonesia, 2008)
Purpose of research is to express elements comprehended as legal capital of trade done by moslem public Gu-Lakudo. Research method. Approach which grounded theory based on phenomenon, with model grounded research and more emphasizing atly is approach of emic. Data collecting is done with method: observation, interview and documentation. Main instrument is researcher self with help: jotter, tape recorde. handycam, and camera, Authenticity of data is tested with triangulation method: technique, source, and time. Data analysis applied constant comparability analysis (constant comparative analysis). Research finds that elements told by legal capital in understanding of moslem public Gu-Lakudo which implementing trade business covers element of matter and element non matter covers: sincerity, godlyr (shalat and zakat). intention prayer, bravery and patient. Integrated the elements is build the capital concept, hence called religious capital. Its defined as wealth of matter and non matter applied (accompanies) to water down effort for man for the agenda of creating highest man value in God eye through mechanism of market diridhai by God.